The twelve days of Christmas - Pizzoli, Greg (Los Angeles ; New York : Disney - Hyperion, 2017)
An elephant parent has to take responsibility for caring for all of the gifts that arrive in this newly illustrated version of the traditional song.
Keywords: Folk songs, English -- Texts; Folk songs -- England; Christmas music